Penyuluhan Pengelolaan Sampah Dengan Konsep 3R (Reduce, Reuse, Recycle) Di Kelurahan Puday Kecamatan Abeli Kota Kendari - Ndibale, Wa; Nahdatunnisa (Amaliah: Jurnal Pengabdian Masyarakat, 2017)
Community serviceoutreach activitiescarried outin the village Puday Abeli District of Kendari, the title 3Rwaste management concept. Garbage does not mean something that can not be reused or recycled. In general litter comes from activities carried out by human beings, including industrial activity. Garbage can not be separated from the waste, but in dealing with waste has a different treatment. Waste sourced directly from industrial activities that waste be produced in conjunction with the ongoing production process, where waste products and are present at the same time. All community out reach expectexpectation Puday Village can implement waste management 3Rconcept, the survey method. Extension activities highly appreciated by the local village chief and village community Puday. The potential sustainability ofthe programare outlined in two different potential, namely the potential sustainability of shortterm programs include the Village People Puday can manageits waste, respectively, sortingtrash from the source, preparelug garbage, throw garbage in landfill (Tempat pembuangan sampah), and reduce was test arts from home, respectively. While the potential llong-term sustainability of the program, including separation of organic waste can be usedas raw material for biogas and inorganic waste used as handicrafts economic value. Thus Puday Village communitycan minimize waste generation and waste management implement the 3Rconcept.